Posterior shoulder fracture-dislocation: double approach treatment. Our experience - Fiorentino, Gennaro; Cepparulo, Riccardo; Lunini, Enricomaria; Guardoli, Alberto; Berni, Luca; Fontanarosa, Alberto; Guardoli, Aldo (Acta Biomedica Atenei Parmensis, 2016)
Background: About 4% of glenohumeral dislocations are posterior and only 1% is associated with fracture of the humeral head. Most frequent causes are high energy traumas, seizures and electrocution. The fracture and the posterior dislocation, associated with the trauma and capsular lesion can cause an important vascular damage of the humeral head. Methods: We describe 5 cases of posterior fracture-dislocation of the shoulder that required open reduction and internal fixation treated using double approach: posterior approach for reduction humeral head and eventually bone and capsular posterior repair and anterior approach for osteosynthesis. A Clinical examination was performed at one year and follow-up was at two years.Conclusions: This combined approach is less invasive, easier for dislocation reduction of the humeral head, with minimal biological damage that may occur during the reduction maneuvers. Our thought is that the posterior approach reduce vascular and bone damages during humeral head reduction and permit to suture and retention posterior capsula that is often damaged by the trauma.